Kriptografija, anonimizacija in odprta koda kot boji za svobodo na internetu - Kovačič, Matej (Javnost (Ljubljana), 2006)
Soon after cryptography became a matter of interest of independent researchers and private companies in 1960's, it also became commonly available.The U. S. government tried to restrict its use. Yet with the emergence of the Internet and wide accessibility of information and communication technology, cryptography became political technology. The battle for public accessible cryptography became a battle for privacy and freedom of individuals. Attempts to ban encryption were not successful. Cryptography spread widely mostly as an effective protection of electronic transactions and commerce rather than a technology of protection of individual rights and freedoms. Today it seems that cryptography does not assure adequate level of privacy by itself, and the battle for privacy and freedom is far from being won. It is directed to transparency of information and communication systems with the aim to achieve a free access to source code of computer applications and to curb secret surveillance mechanisms. Another battle takes place in the field of anonymisation systems as mechanisms for maintaining civil liberties on-line. Mass and automatic surveillance is enabled by analyses of traffic data. Recent legislative amendments that require data retention increase the effectiveness of surveillance technologies. Yet despite of the development of several privacy protecting technologies, most of individuals voluntarily waive their privacy and freedom - for the sake of convenience and because of the lack of concern.
Keywords: računalniške komunikacije; računalniška omrežja; internet; privacy; zasebnost; varstvo podatkov; človekove pravice; human rights; kriptografija; kodiranje